REDEFINISI JARING KONTROL VERTIKAL DAN HORIZONTAL KAMPUS ITB GANESHA - Najmi Naufal, Muhammad
There are many geodesy control points located within the area of ITB Ganesha Campus, each has a certain coordinates in the vertical and horizontal planes that are interconnected by a vertical and horizontal control network. Control point coordinates are defined in a particular reference system. The reference system currently used in Indonesia is the 2013 Indonesian Geospatial Reference System (SRGI 2013). At present, the coordinates of the ITB Ganesha Campus control points do not refer to SRGI 2013, but a vertical and a horizontal control network measurement data are available from a survey conducted by the author. Therefore, a study will be conducted that aim to determine the vertical and horizontal coordinates of the ITB Ganesha Campus control points in SRGI 2013. From this study, the quality of the surveyed measurement data and the quality of the control point vertical and horizontal coordinate data can be known. The acquisition of the vertical and horizontal control network measurement data were carried out using the leveling and traverse method. Then the determination of vertical and horizontal coordinates is done by the least square adjustment method. This research succeesfully produces the vertical and horizontal coordinates of the ITB Ganesha Campus control points in SRGI 2013. The quality of the vertical and horizontal control network data have fulfilled the provisions of the LC-class of SNI 19-6988-2004 and the 4th order of SNI 19-6724-2002, have good precision, with no suspected blunders based on statistical test and validation results. The resulting control point coordinates have a mean vertical and horizontal standard deviation in the 95% confidence interval of 4.10 mm and 8.27 mm, with the standard deviation normally distributed in the 95% confidence interval. It is known that the precision and accuracy of these horizontal coordinates are better than the coordinates from RTK GNSS observations when both are compared against the coordinates from static GNSS observations based on the sample coordinates used in validation.